2020
DOI: 10.18632/oncoscience.504
|View full text |Cite
|
Sign up to set email alerts
|

HUNK Signaling in Metastatic Breast Cancer

Abstract: Once metastatic disease has occurred, there is no cure for breast cancer. Consequently, identifying factors that promote and support breast cancer metastasis is critical for understanding how to pharmacologically target this process. Hormonally up-regulated neu-associated kinase (HUNK) is a serine/threonine protein kinase related to the sucrose non-fermenting-1 (Snf-1)/5' adenosine monophosphate-activated protein kinase (AMPK) family of kinases. HUNK has been found to play a role in breast cancer metastasis. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Combined with GWAS results, 20 genes were simultaneously identified through GWAS and Fst analysis, out of them, SCAF4 , SOD1 , and TIAM1 were detected in two GWASs, and ENSSSCG00000048838 , ENSSSCG00000047227 , ENSSSCG00000043944 , ENSSSCG00000048577 , ENSSSCG00000042932 , ENSSSCG00000041405 , and ENSSSCG00000045589 were the novel genes. HUNK was involved in transferase activity, transfer phosphorus-containing groups, and protein tyrosine kinase activity, and was thought to play a role in breast cancer metastasis ( Dilday et al, 2020 ; Williams et al, 2020 ). ARHGDIB , RERG , and TMEM170B were also related to breast cancer ( Li et al, 2018 ; Huang et al, 2020 ; Wang et al, 2020 ), implying they might participate in the development of mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with GWAS results, 20 genes were simultaneously identified through GWAS and Fst analysis, out of them, SCAF4 , SOD1 , and TIAM1 were detected in two GWASs, and ENSSSCG00000048838 , ENSSSCG00000047227 , ENSSSCG00000043944 , ENSSSCG00000048577 , ENSSSCG00000042932 , ENSSSCG00000041405 , and ENSSSCG00000045589 were the novel genes. HUNK was involved in transferase activity, transfer phosphorus-containing groups, and protein tyrosine kinase activity, and was thought to play a role in breast cancer metastasis ( Dilday et al, 2020 ; Williams et al, 2020 ). ARHGDIB , RERG , and TMEM170B were also related to breast cancer ( Li et al, 2018 ; Huang et al, 2020 ; Wang et al, 2020 ), implying they might participate in the development of mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…HUNK is a serine/threonine kinase, and plays an important role in many cancer types, including CRC [ 7 , 24 ]. We speculated that HUNK exerts its biological functions through its kinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…HUNK plays an important role in cancer cell proliferation, survival, as well as metastasis, and is an emerging therapeutic target for cancer treatments [ 7 , 8 , 10 , 28 32 ]. Clinically, we showed that HUNK protein levels are downregulated in metastatic CRC tissues in contrast to primary CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonally upregulated neu-associated kinase (HUNK) is an approximately ~80 kDa serine/threonine (S/T) protein kinase that has been reported to be expressed in about 50% of breast carcinomas [ 1 , 2 , 3 , 4 ]. HUNK is part of the AMP-associated protein kinase (AMPK) family and plays a role in a variety of cellular processes, including the regulation of cell survival, proliferation, and autophagy [ 1 , 5 ]. While this protein was originally discovered in mouse mammary glands and is expressed in breast tissue, it has also been found in other organ systems such as the brain and central nervous system, and plays a role in diseases including colon cancer [ 3 , 4 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%